Uso de lipase vegetal a partir de sementes de mamona para a hidrólise enzimática de óleo de crambe - Tavares, Fernanda (2018)
Lipases are a class of enzymes responsible for breaking down the ester bonds of triglycerides; they can derivate from microbial, animal or vegetal origin, the last ones can be found mainly from the germination processes of oilseeds. Castor bean seeds have the advantage of having lipases in its composition even in non-germinated state. In this sense, the present work aims to evaluate the use of castor bean as a source of lipase in the hydrolysis of triglycerides to obtain free fatty acids, employing sonication and orbital agitation system, investigating the use of in natura seeds and seeds after oil extraction process, to enable its commercial use. In addition, the crambe oil is employed, an oil that is rich in monosaturated free fatty acids, easy obtainment and it is has no use in the food chain. Using CCRD experimental designs an optimum point was found for in natura seeds in the condition of temperature of 33 °C, 0.87 buffer/oil (m/m) and 0.31 catalyst/substrate (m/m) reaching a yield of 91% after 4 hours of reaction; for the incubated seeds the optimum condition was in the temperature of 43.8 °C, 1.8 buffer/oil (m/m) and 0.07 catalyst/substrate (m/m) in which approximately 88% yield was achieved after 4 hours of reaction. In order to optimize the reaction conditions, the use of ultrasound in the enzymatic hydrolysis was evaluated, as optimal conditions were approximately 70% of ultrasound power, 1.79 buffer/oil (m/m), 0.25 catalyst/substrate (m/m) for the in natura seeds, achieving approximately 86% of yield after 5 minutes of ultrasonic reaction and 91% after more 30 minutes of reaction with mechanical stirring and for incubated seeds approximately 68% of ultrasound power, 1.67 buffer/oil (m/m), 0.06 catalyst/substrate (m/m), reaching 73% of yield after 5 minutes of ultrasonic reaction and 77% after more 30 minutes of reaction with mechanical stirring. The best yield, therefore, was verified when in natura seeds were employed; these seeds don’t go through any preparation process and have emulsifying components that can help in the triglycerides hydrolysis. Besides that, a mathematical model was proposed and it was satisfactory to predict the experimental data of crambe oil enzymatic hydrolysis when in natura and incubated seeds were employed in mechanical-orbital agitation reactions and with ultrasonic emulsification. In this sense, the contribution of the present work is to give a better understanding for the enzymatic hydrolysis of triglycerides with the utilization of vegetal lipases from castor seeds, and employing an oil that has not been yet well studied and utilized.